Comparison of Psycho-Social Factors Associated With Suicidal Ideation and Suicide Attempts Among People Living With HIV in Central West China - Wang, Xuelian; Yan, Chuanyuan; Tong, Yongsheng; Gao, Juan; Zhou, Wei; Lan, Zhichao; Wu, Jianlan; Li, Hongbing; Yin, Yi; Wang, Yuehua; Liu, Nancy H.; Deng, Feng (Frontiers in Public Health, 2022)
Background: Previous studies have described correlates of suicidal ideation (SI) or suicide attempts (SA) in people living with HIV (PLWH), whereas few studies compare correlates of SI and that of SA in PLWH. Understanding specific risk factors for SI and SA among PLWH will help with developing tailored, effective suicide prevention strategies among this high-risk group. Methods: A cross-sectional study was conducted from December 2020 to April 2021in Baoji municipality, Shaanxi Province. PLWH registered with the Baoji Municipal Center for Disease Control and Prevention (CDC) were recruited and interviewed. Questionnaires and interviews for this study consisted of socio-demographic variables, mental health history, and psychosocial characteristics. HIV-related clinical features were obtained from CDC medical records. Included PLWH were divided into three groups, i.e., those with any suicide attempt (SA group), those with suicidal ideation only (SI group), and those without any suicidal behavior (NSB group). Multinomial logistic regression was used for three-way comparisons among these three groups of PLWH. Results: In total, 995 PLWH were interviewed. The prevalence of probable depression, probable anxiety, SI, and SA in PLWH after being diagnosed as HIV+ was 18.6%, 13.5%, 26.7% and 3.2%, respectively. Compared with the NSB group, the SI or SA groups were more likely to report probable depression (AOR=2.43, 4.44, respectively), probable anxiety (AOR=2.80, 5.62, respectively), and high HIV-related stigma (AOR=2.05, 2.65, respectively). The SI group was more likely to experience high HIV-related stress (AOR=1.91) and lower quality of life (AOR=0.56) than the NSB group. Social support and HIV related clinical features were not associated with SI or SA in this sample. The SA group did not differ from the SI group on any of the psychosocial or HIV-related clinical features. Conclusions: Mental health problems are serious in community residents identified as having an HIV infection in a Central West China municipality. It is important to deliver low-cost, effective psychological services focused on reducing mental health problems and tailored for PLWH. Future studies should utilize sensitive screening measures and further clarify factors potentially associated with the transition from SI to SA in PLWH.